Mobile App Prototype: Telemedicine for Mental Health Care During Pandemic - Jauregui-Velarde, Raul (2023)
Since the end of 2019, the contagious disease COVID-19, which originated in the city of Wuhan, China; It affected every country in the world. As a measure to prevent the spread of the virus, the Peruvian government ordered quarantine and social distancing; As a consequence, people's economy and social life were affected, increasing stress, depression and anxiety, which are emotional disorders that affect mental health. Added to this is the lack of access to mental health services. The objective is to develop a prototype mobile telemedicine application for mental health services, based on Android. The methodology that was applied was the Rational Unified Process (RUP) methodology, because this methodology allows documenting, ordering and structuring software development. The result obtained was a telemedicine mobile application prototype with a design and functionalities that facilitate the access of patients and specialists to provide mental health services. The evaluation of the quality of the prototype was carried out through the judgment of experts, who evaluated the efficiency, usability and security of the application. Obtaining after the calculation, 4.66 average or mean; which indicates, according to the established quality range, that the quality of the mobile prototype is high. In conclusion, it was possible to develop an efficient, easy-to-use and safe mobile telemedicine prototype; that provides the solution by facilitating patients' access to mental health services for their emotional, psychological and social well-being.